this could be us : a deep dive into the creative process - Lolli, Giorgia (My University, 2025)
This thesis generates discourse around this could be us, situating its creative process within broader choreographic discourses. Structured in three acts - framed by an Overture and a final outlook - the text progressively approaches the staged choreographic work through layers of contextual references, theoretical framing, and critical reflection on the making process. A central focus is given to ballet as a material, re-appropriated beyond its traditional disciplinary canon into the spaces of contemporary choreography (examining both my work and selected references: Forsythe, Holzinger, Gribaudi). Within these frames, the writing later reflects on how plurality and embodied agency can emerge as structuring elements of choreographic work. Contextually, angles of feminist theory offer a second framework of analysis to illuminate my choreographic practice: drawing from Judith Butler, Sara Ahmed, and contemporary reflections on comradery, the writing frames the studio as a gendered space and considers the links between choreographic thinking and orientation. Upon having paved a landscape around the creation, attention is also given to compositional, relational, and group-making strategies, and the overall dramaturgy of the staged performance. Altogether, this thesis offers a situated contribution to conversations in dance and choreography from the perspective of the maker. It extends the choreographic process into writing, positioning choreographic creation as a site of experimentation and proposing a deep dive through which an embodied process can articulate itself from within into a written landscape.
Keywords: subtraction; agency; soft skills; relationality; difference; choreography; dance; ballet (art forms); performance (art forms); fi=koreografia|sv=koreografi|en=Choreography|